Respon Konsumen Terhadap Produk Yotta Rasa Brown Sugar Fresh Milk di Kabupaten Maros - Miftahul Janna; Mohammad Anwar Sadat; Arifin Arifin (Jurnal Agribis, 2023)
The purpose of this study is to identify the variables that influence Maros Regency consumers' reactions to Yotta Beverage products. Direct observation and questionnaire data collection were used in this study. The study took place over a three-month period from March to May, and was conducted in Turikale Sub-district, Maros Regency. To determine customer reactions to Brown Sugar Fresh Milk flavored Yotta products in Turikale Sub-district, Maros Regency, quantitative data was used. Based on the research findings, price and taste are the main determinants of Yotta Taste Brown Sugar Fresh Milk in Turikale District, Maros Regency.